Reality counseling to increase student resilience of self injury victims - Salmi Salmi (Indonesian Institute for Counseling, Education and Theraphy, 2021)
The victim of self injury shows the trait of injuring a limb with the intention of not killing to release emotional tension. This results in the client feeling the problem is getting heavier, withdrawing from his environment when there is a problem and venting by doing self-injuiry. Conscious clients begin to abandon this behavior and develop the ability to remain calm under stressful conditions known as resilience. Self injuiry which can cause addiction when there is a serious problem needs to be given assistance efforts to increase the resilience of victims of self injuiry. Integration of reality counseling is important to do because it is related to the ability of 3R (righ, reality and responsibility) clients as well as success identity and failure identity so that clients are able to increase their resilience. This qualitative research uses a case study approach with the subject of a 15 year old self-injury victim. Data was extracted by observations and interviews analyzed by data reduction, data presentation and conclusion drawing. The results showed that reality counseling can help increase the resilience of victims of self-injury.